Update on emerging treatments for chronic myeloid leukemia. (June 2015) - Fava, Carmen; Morotti, Alessandro; Dogliotti, Irene; Saglio, Giuseppe; Rege-Cambrin, Giovanna
<x xml:space="preserve">Abstract</x> Introduction: As survival of patients with chronic myeloid leukemia (CML) is dramatically improved over time, the prevalence of the disease is steadily increasing. At this moment, five different tyrosine kinase inhibitors (TKIs) (imatinib, nilotinib, dasatinib, bosutinib and ponatinib) are approved for the treatment of CML. Medical and patients needs nowadays are attention to quality of life (QoL) and drug side effects; overcoming suboptimal responses; preventing progression and possibly discontinuing the drugs. Monitoring is essential to improve on treatment and on the possibility of cure, because it allows patient adapted therapies, according to patients morbidities and early responses. Areas covered: This review focuses on clinical results of imatinib and second- and third-generation TKIs that have been tested in the setting of second-line and front-line treatments. The most promising new drugs in course of clinical investigations are also reported. Expert opinion: The scientific community is focusing on the optimization of the use of the drugs already available, to be also used in association with other experimental drugs directed to several signaling transduction pathways of BCR-ABL, in order to improve the efficacy on resistant cases, and on leukemic stem cells, keeping in mind the issues of long-term safety, QoL and the need for treatment – free remission.